TINGKAT KEPATUHAN PEMAKAIAN ALAT PELINDUNG DIRI DENGAN PENGETAHUAN DALAM PENCEGAH COVID-19 PADA STAFF DI PUSAT KESEHATAN MASYARAKAT PLAJU PALEMBANG TAHUN 2022 - AFWAN SYARIF (Avicenna: Jurnal Ilmiah, 2022)
Background: The SARS-COV 2 virus and the corona virus are the causes of Corona Virus Disease-19 (Covid-19), an infectious disease with mild to severe symptoms. The purpose of this study is to ascertain the degree to which Plaju Palembang Public Health Center staff adhere to the use of personal protective equipment (PPE) for the purpose of preventing Covid-19. Methods: A cross-sectional approach to a quantitative research design that employs an analytical and descriptive approach. All Plaju Public Health Center staff were included in this study's population. Results: According to the findings of this study, there was a significant relationship (p=0.000) between staff at the Health Center The people of Plaju Palembang's knowledge and adherence to the use of personal protective equipment (PPE) to prevent Covid-19. In this study, employees at the Plaju Palembang Public Health Center were found to be more likely to adhere to the use of personal protective equipment (PPE) to prevent Covid-19.